Petroglyphs and tamgas of the Eurasian area as archetypes of Turkic culture and script - Shaimerdinova, Нурила; Moldabay, Талгат (Turkic Studies Journal, 2023)
The paper is devoted to the problems of the origin and connection of the Turkic culture and script with the most ancient petroglyphs, tamgas, and logograms. Researchers believe that since the Paleolithic era, petroglyphs, tamgas, signs have been widely spread on a vast territory of Eurasian area. In this context, the authors studied and systematized plot drawings, and signs-symbols of Kazakhstan, Mongolia, Kyrgyzstan, Uzbekistan, Azerbaijan, Turkey, Russia (Tyva, Khakassia, Gorny Altai, Transbaikalia). The article hypothesizes that the oldest signs could be the basis for the formation of the Turkic script, and revealing their historical, cultural and semantic connection, classify archetypes into cruciform ( signs and their letter designations by consonants «d» and «z»), religious-cult, temporalcosmological, anthropomorphic, and the signs prototypes of the Turkic nomadic culture (arba, weapons, wildlife). Semantic analysis of archetypes is important for the identification of ancient man’s perceptions about the world around him. The archetypes of nomadic culture reveal the way of life and the worldview of ancient people. The paper asserts that the process of historical development of Turkic culture and script for thousands of years, starting from its origins, can be considered as an autochthonous phenomenon of the Turkic civilization.